Reconstructing the Role of Al-‘Adah Muhakkamah in Islamic Criminal Law: An Integrative Framework of Naṣṣ, Living Law, and Maqāṣid al-Sharī‘ah - Bahatma Baca; Muhammad Taufiq Nasution; Mulkan Nasution; Fauzan Mas’ar (Yayasan Dar Arrisyah Indonesia, 2026)
The increasing complexity of contemporary society has generated new forms of criminal conduct that cannot always be addressed adequately through the classical formulation of Islamic criminal law. This condition requires a methodological framework capable of preserving the normative authority of the Qur'an and Sunnah while accommodating dynamic social realities. Although the legal maxim al-'adah muhakkamah (custom is recognized as a legal consideration) has long been acknowledged as one of the fundamental principles of Islamic legal maxims (qawā'id fiqhiyyah), limited scholarly attention has been devoted to reconstructing its function as an integrative instrument connecting nash, living law, and maqāṣid al-syarī'ah in contemporary Islamic criminal law. This study aims to reconstruct the function of al-'adah muhakkamah as a methodological framework for harmonizing normative Islamic legal authority with evolving social realities. This research employs normative legal research using conceptual, statutory, and philosophical approaches through qualitative library research based on classical juristic works, uṣūl al-fiqh, qawā'id fiqhiyyah, legislation, and recent scholarly publications. The findings demonstrate that al-'adah muhakkamah should no longer be viewed merely as a supplementary legal maxim but as an epistemological bridge integrating scriptural authority, the objectives of Islamic law (maqāṣid al-syarī'ah), and living law. Such reconstruction enables Islamic criminal law, particularly within the sphere of jarīmah ta'zīr, to respond adaptively to contemporary crimes while maintaining immutable Islamic legal principles (tsawābit). This study proposes an integrative model positioning al-'adah muhakkamah as the methodological nexus between universal Islamic legal norms and contemporary social realities, thereby strengthening the adaptability and sustainability of Islamic criminal law in modern society.